Impact of clinical pharmacist intervention on blood glucose control and perinatal outcomes in gestational diabetes mellitus through a diabetes management system - C. Ji; L.J. Sun; L.T. Li; J. Ma; W.H. Ge; X. Zhao (IMR Press, 2020)
Background: Very few studies have assessed the role of a clinical pharmacist in women with gestational diabetes mellitus (GDM). To improve pharmaceutical care, we explored a method to improve the control of blood glucose and perinatal outcomes in females with GDM through the application of a diabetes management system. Methods: A randomized controlled trial was conducted from October 2017 to October 2018 for 200 outpatients with GDM. In the study, a diabetes management system with pharmaceutical care was used for the intervention group. The clinical outcomes of all patients were recorded at the end of delivery. Results: From one sample of 200 patients, 169 finished the research. Compared with the control group, patients in the intervention group manifested greater reductions in fasting plasma glucose (5.22 ± 0.37 vs. 6.05 ± 1.06 mmol/L; P = 0.018), 2 h postprandial plasma glucose (6.66 ± 0.57 vs. 9.69 ± 1.58 mmol/L; P = 0.00), and glycated hemoglobin A1c corrected values (1.02 ± 0.12 vs. 1.16 ± 0.22; P = 0.023). Moreover, the rate of polyhydramnios was significantly lower in the intervention group than in the control group (0% vs. 10.59%; P = 0.003) as well as significantly fewer macrosomia in the intervention group (7.14% vs. 18.82%; P = 0.038). Conclusions: Using a diabetes management system, clinical pharmacists can improve the control of blood glucose and perinatal results in GDM females. With a diabetes management system, the comprehensive management of GDM is a new model for pharmaceutical care in the future.